2012
DOI: 10.1093/jrr/rrs053
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of double dose contrast-enhanced magnetic resonance imaging for clear delineation of gross tumor volume in stereotactic radiotherapy treatment planning of metastatic brain tumors: a dose comparison study

Abstract: The purpose of this study was to compare the size and clearness of gross tumor volumes (GTVs) of metastatic brain tumors on T1-weighted magnetic resonance images between a single dose contrast administration protocol and a double dose contrast administration protocol to determine the optimum dose of contrast-enhancement for clear delineation of GTV in stereotactic radiotherapy (SRT). A total of 28 small metastatic brain tumors were evaluated in 13 patients by intra-individual comparison of GTV measurements usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…5). This is in line with several studies demonstrating a higher sensitivity for detecting small metastases using double or triple doses of GBCA 43–46 . Similar contrast (tumor-to-brain) was observed for gadoquatrane at a less than 75% of the Gd dose (more than 90% less for molecule dose) compared with the standard dose of gadoterate meglumine (0.1 mmol Gd/kg bw) (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…5). This is in line with several studies demonstrating a higher sensitivity for detecting small metastases using double or triple doses of GBCA 43–46 . Similar contrast (tumor-to-brain) was observed for gadoquatrane at a less than 75% of the Gd dose (more than 90% less for molecule dose) compared with the standard dose of gadoterate meglumine (0.1 mmol Gd/kg bw) (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…4 One obvious way of dealing with this issue is to increase the longitudinal relaxivity of GBCAs to increase the contrast between the lesion and background healthy parenchyma with the classic dose of 0.1 mmol Gd/kg. 25,26 A sufficient relaxivity increase could even enable reduction of the Gd dose without lowering the current efficacy associated with extracellular and nonspecific GBCAs. 4 All extracellular GBCAs currently on the market have roughly similar relaxivity properties, 27 and their use at higher doses is limited due to potential safety concerns.…”
mentioning
confidence: 99%
“…At the same time, it has been known for a long time that the detection of small contrast-enhancing lesions is strongly dependent on the contrast dose, leading to the partial use of double-dose protocols in brain MRI to increase sensitivity. [33][34][35] In this regard, a study by Haubold et al 10 aimed to compare 2 reduction levels of intravenous ICM dose (100% dose corresponds to 1.5 mL/kg iopromide 300 mg I/mL [Ultravist 300; Bayer Vital GmbH, Leverkusen, Germany]) in CT using GANs. The authors reported that a 50% reduction in ICM dose could be achieved while maintaining image quality and consistency in the visualization of pathologies, whereas an 80% reduction negatively affected the consistency of the visualization of pathologies in CT imaging despite similar results of the quantitative image similarity evaluation.…”
Section: New Frontiers In Contrast Agent Dose Reductionmentioning
confidence: 99%
“…One example is the search for brain metastases, where it has long been known that doubling the dose can significantly increase the sensitivity in detecting metastases. 33,34 In this regard, recent studies have shown that such approaches may increase the sensitivity of radiologists in the detection of cerebral metastases. 2 Table 1 shows the publications in the 3 frontiers of AI in contrast media research.…”
Section: New Applicationsmentioning
confidence: 99%